Motor function of the proximal stomach and visceral perception in gastro-oesophageal reflux disease. Issue 2 (1st February 1998) - Penagini, R; Hebbard, G; Horowitz, M; Dent, J; Bermingham, H; Jones, K; Holloway, R H
Abstract : Background —The abnormally high postprandial rate of transient lower oesophageal sphincter relaxations seen in patients with reflux disease may be related to altered proximal gastric motor function. Heightened visceral sensitivity may also contribute to reporting of symptoms in these patients. Aims —To assess motor function of the proximal stomach and visceral perception in reflux disease with a barostat. Methods— Fasting and postprandial proximal gastric motility, sensation, and symptoms were measured in nine patients with reflux disease and nine healthy subjects. Gastric emptying of solids and liquids was assessed in six of the patients on a different day (and compared to historical controls). Results— Minimal distending pressure and gastric compliance were similar in the two groups, whereas the patients experienced fullness at lower pressures (p<0.05) and discomfort at lower balloon volumes (p<0.005) during isobaric and isovolumetric distensions respectively. Maximal gastric relaxation induced by the meal was similar in the two groups. Late after the meal, however, proximal gastric tone was lower (p<0.01) and the score for fullness higher (p<0.01) in the reflux patients, in whom the retention of both solids and liquids in the proximal stomach was greater (p<0.05). Conclusions —Reflux disease is associated with delayed recovery of proximal gastric tone after a meal and increased visceral sensitivity. The former may contribute to the increased prevalence of reflux during transient lower oesophageal sphincter relaxations and the delay in emptying from the proximal stomach, whereas both may contribute to symptom reporting.